Feeding sorghum stover to Ethiopian goats and sheep: Effect of amount offered on growth, intake and selection - Aboud, A.A.O.; Owen, E.; Reed, J.D.; Said, A.N.; McAllan, A.B. (International Goat Association, 1993)
Twenty four male goats and 24 rams were individually fed 150g cottonseed-cake/day and, offered 25, 50 or 75 g sorghum stover per kg M daily over 75 days following a preliminary period of 21 days. Stover was offered in chopped form. Live-weight gain of sheep was higher than of goats; there was no interaction between species and amount of stover offered. Growth rate increased with increasing amount of stover offered. Stover intake was higher for sheep than for goats, and there was no interaction of species with amount of stover offered. The proportion of offered stover remaining uneaten increased with increasing amounts offered. The proportions of leaf and leaf-sheath in uneaten stover decreased with decreasing amounts of stover offered. The data indicated that both goats and sheep and capable of selective feeding, leading to increased intake and growth, when they are offered increasing ad lib. amounts of chopped sorghum stover.